234k views
0 votes
12=-4(-6x-3) please help

User Philomath
by
4.5k points

2 Answers

4 votes

Explanation:

12=-4(-6x-3)

when minus is multiplied by minus then the result is plus,

12=24x+12

Now, subtract 12 from both sides,

12-12=24x+12-12

0=24x

Now, divide both sides by 24

0/24=24x/24

0=x

User Jhonnatan
by
5.1k points
4 votes

Answer and Step-by-step explanation:

First, distribute the negative 4 onto the negative 6x and negative 3.

12 = 24x + 12

Subtract 12 from both sides of the equation.

0 = 24x

Divide both sides of the equation by 24.

x = 0

To check our answer:

-4(-6(0) - 3) = 12

-4(0 - 3) = 12

-4(-3) = 12

12 = 12 ✓

So, x is equal to 0.

#teamtrees #PAW (Plant And Water)

I hope this helps!

User Aleks Vujic
by
4.8k points